THE IMPACT OF SERVICE QUALITY, PROMOTION, AND PRICE PERCEPTIONS ON USER SATISFACTION OF SOLO-YOGYAKARTA ELECTRIC RAIL TRAIN - Intan Ayu Prawesti; Bambang Mursito; Fithri Setya Marwati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study intends to ascertain the impact of service quality, promotion, and price perceptions on user satisfaction of the Solo-Yogyakarta Electric Rail Train. This study employed a descriptive quantitative methodology. All passengers on the Solo-Yogyakarta Electric Rail Train (KRL) made up the study's population. Purposive sampling is used in the sampling process, yielding 100 responders as samples. The methods for data analysis that are being employed are multiple linear regression analysis, t test, and coefficient of determination. According to the findings, user satisfaction with the Solo-Yogyakarta Electric Rail Train was positively and significantly impacted by service quality, promotion, and price perceptions. The results of the coefficient of determination test (R2) computation yielded a value of 0.605. This demonstrates that of the variation in the dependent variable (customer satisfaction), 60.5% can be accounted for by service quality, promotion, and price perceptions, with the remaining 39.5% being influenced by additional variables not taken into account by the research. Keywords: customer satisfaction, service quality, promotion, and price perceptions